An electrolyte-free electrochromic device using aluminum as counter electrode material - Gusatti, Marivone [UNESP]; Souza, Daniel A.R. [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Nalin, Marcelo [UNESP] (Elsevier, 2023)
In this study, a novel all-solid-state electrochromic device (ECD) free of indium tin oxide (ITO), tungsten(VI) oxide (WO3), and Li+ or any other liquid/gel electrolytes was prepared by a cost-effective and industrially applicable spray coating technique. The device configuration consists of a pre-formed Al-coated glass substrate for use as a counter electrode in the fabrication of an ECD with a glass/Al/Alq3/PEDOT:PSS structure. The fabricated device (2.5 × 4.0 cm2) demonstrated a reversible color change between a light-blue (off) and dark-blue (on) state, with good and homogeneous contrast. The ECD started coloring at − 0.5 V and was completely colored at – 2.0 V, showing various tones of blue according to the applied voltages. The coloration efficiency was 174.62 cm2/C and the cycle stability was achieved at least 150 times.
Keywords: Al counter electrode; All-solid-state electrochromic device; ITO-Free ECD; PEDOT-Based device; Spray coating technique